South China Sea territorial & jurisdictional disputes: the way forward - Ahmad, Muhamad Hassan (2018)
Competing territorial and boundary claims over the various maritime features in the South China Sea among the disputing parties, namely, Brunei, China, Malaysia, Taiwan, the Philippines and Vietnam have been one of the most contentious issues for some decades. Despite the fact that these nations have been trying to resolve the disputes, tensions among the rival countries have steadily increased. Accordingly, this paper predominantly aims at evaluating the territorial claims made by China in the South China Sea as to whether or not these claims are in accordance with the contemporary international law. The author proposes that the adjudicative settlement either before the International Court of Justice (ICJ), the International Tribunal for the Law of the Sea (ITLOS) or an ad hoc international territorial arbitration would be desirable between or among the parties to deliberate further on the disputes with the view to maintain the international peace and security.